Effects of the novel polyphenol conjugate DPP-23 on head and neck squamous cell carcinoma cells in vitro - Taeger, J; Scherzad, A; Feineis, D; Seupel, R; Hagen, R; Kleinsasser, N; Hackenberg, S (Spandidos Publications, 2018)
Despite partial advances in therapy for patients suffering from head and neck squamous cell carcinomas (HNSCC), prognosis still remains poor with minimal improvement in survival for over the last several decades. Some agents found are known to cause cancer cell death in vitro by promoting cellular reactive oxygen species (ROS) accumulation. This is particularly of interest as some cancer cells are more sensitive to ROS than normal cells. It could be shown that the novel polyphenol conjugate (E)-3-(3',5'-Dimethoxyphenyl)-1-(2'-methoxyphenyl)prop-2-en-1-one (DPP-23) offers antitumor effects by the selective generation of ROS without an indication of toxicity in normal tissues in vitro and in vivo. In order to further evaluate the role of DPP-23 as a potential agent in head and neck oncology, the present study investigated its cytotoxic effects on well-established HNSCC cell lines such as HLaC 78 and FaDu, as well as primary human bone marrow stem cells (hBMSCs) and human peripheral blood lymphocytes in vitro. As DPP-23 is not commercially available, it was synthesized via a 'cold' procedure of the Claisen-Schmidt condensation. Following cell treatment with DPP-23 for 24 h, viability and apoptosis were measured via a MTT assay and the Annexin V-propidium iodide test. The results suggest a dose-dependent cytotoxicity in the tested HNSCC tumor cell lines, as well as in hBMSC and lymphocytes. In contrast to previous findings, these preliminary results indicate that the cytotoxic effects of DPP-23 in benign cells may be notably greater than previously suspected. This may indicate a limitation for in the feasibility, or at least of the systemic application, of DPP-23 for patients with HNSCC.